2021
DOI: 10.1038/s41598-021-82996-6
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the large carnivore community structure of the Judean Desert in connection to Holocene human settlement dynamics

Abstract: Investigating historical anthropogenic impacts on faunal communities is key to understanding present patterns of biodiversity and holds important implications for conservation biology. While several studies have demonstrated the human role in the extinction of large herbivores, effective methods to study human interference on large carnivores in the past are limited by the small number of carnivoran remains in the paleozoological record. Here, we integrate a systematic paleozoological survey of biogenic cave a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 17 publications
(30 citation statements)
references
References 66 publications
(98 reference statements)
3
27
0
Order By: Relevance
“…There, the punctuated settlement history at the major oasis in the region, Ein Gedi, is known from years of survey and excavations and is supplemented by historical sources (Hadas, 2005; Davidovich, 2013; Ussishkin, 2014). This archaeological settlement record is matched by well‐preserved biogenic assemblages of faunal remains found in the hundreds of karstic caves dotting the high‐relief topography of the region (Horwitz et al, 2002; Frumkin, 2015; Lazagabaster et al, 2021a,b). Together, the archaeological and paleozoological data provide an opportunity to study Holocene wild mammal communities from a binocular perspective, against the background of environmental studies that have been conducted in the Dead Sea (e.g.…”
Section: Introductionsupporting
confidence: 54%
“…There, the punctuated settlement history at the major oasis in the region, Ein Gedi, is known from years of survey and excavations and is supplemented by historical sources (Hadas, 2005; Davidovich, 2013; Ussishkin, 2014). This archaeological settlement record is matched by well‐preserved biogenic assemblages of faunal remains found in the hundreds of karstic caves dotting the high‐relief topography of the region (Horwitz et al, 2002; Frumkin, 2015; Lazagabaster et al, 2021a,b). Together, the archaeological and paleozoological data provide an opportunity to study Holocene wild mammal communities from a binocular perspective, against the background of environmental studies that have been conducted in the Dead Sea (e.g.…”
Section: Introductionsupporting
confidence: 54%
“…Therefore, the bioturbated sediments retain almost no stratigraphic context (29). Remains of L. i. maremortum subsp.…”
Section: Resultsmentioning
confidence: 99%
“…nov. likely survived in refugial areas, taking advantage of water springs, developed Acacia woodland, and patches of Mediterranean and tropical vegetation relics in the Dead Sea area (SI Appendix, Text S14). A few humid and vegetated refugia persist nowadays in association with water springs and Sudanian floral elements, like the Ein Gedi oasis (29,45). Suitable habitats for Lophiomys must have been present at least until ∼42 ka as the climate deteriorated with the advent of the LGM and the spread of Irano-Turanian steppe biome (46).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, other recent studies have demonstrated the potential of carnivore dens for the study of prehistory and paleoecology, particularly in arid regions where suitable archives are often scarce. By studying carnivore dens in the Judean Desert, Lazagabaster et al (2021) showed that a shift in large carnivore community structure-namely the replacement of Arabian leopards with striped hyena as the dominate large carnivore in the landscape-coincided with an increase in human presence in the region, which they attribute to the active hunting of leopards and an increase in livestock scavenging opportunities for striped hyena. While authors of another recent study of striped hyena coprolites from central Iran argued that the "pollen encapsulated in these coprolites can be a major source of information on their environments, their foraging behavior and diet, as well as their interactions with human societies in the far and recent past" (Djamali et al 2020 p. 17).…”
Section: Implications For Prehistory and Paleoecologymentioning
confidence: 99%